Synthesis of 1-Phenyl-3-(pyridine-4-yl)prop-2-ynyl Acetate - ERENLER, RAMAZAN (Asian Journal of Chemistry, 2010)
The propargyl alcohol (3) was synthesized by the treatment of benzaldehyde (1) with trimethylsilylacetylene and n-butyl lithium in THF at -78ºC. After removing of trimethylsilyl with KOH in MeOH, 1-phenylprop-2-yn-1-ol (4) was obtained. The coupling of this compound 4 with 4-bromopyridine yielded the 1-phenyl-3-(pyridin-4-yl)prop-2-yn-1-ol (5) which was converted to acetate 6 via acetic anhydride.